Recent benthic foraminiferal distribution in the Elbe Estuary (North Sea, Germany): A response to environmental stressors. (5th April 2021) - Francescangeli, Fabio; Milker, Yvonne; Bunzel, Dorothea; Thomas, Helmuth; Norbisrath, Mona; Schönfeld, Joachim; Schmiedl, Gerhard
Abstract: For the past 200 years, estuarine environments experienced intense and rapid environmental degradations due to human interventions. In addition, Global Changes are modifying the estuarine physiography, leading to a re-structuration of marginal marine benthic communities. The aim of this study is to document, the modern assemblage composition and the species-environment relations of benthic foraminifera upstream the Elbe Estuary (southern North Sea) and to observe what has changed since the first survey in 1981. For this purpose, a surface sampling was carried out from 22 stations along the transitional area of the Elbe Estuary. Living (rose-Bengal stained) and dead foraminiferal assemblages were analysed as well as hydrological and sedimentological parameters (such as salinity, pH, grain-size, and organic matter). Living faunas are characterized by very low densities and largely dominated by Ammonia species. Dead assemblages are more diverse and dominated by Ammonia aomoriensis, Haynesina germanica, and Cribroelphidium selseyense. Salinity and grain-size seem to be the major factors influencing foraminiferal distributions in the transitional area. Under the ongoing climate changes, future strategies will be taken to foster the application of benthic foraminifera as biomonitoring tool in the Elbe Estuary, via this baseline investigation. Highlights: Investigations of the benthic foraminiferal distribution in the Elbe Estuary. Low diverse assemblages are dominated by Ammonia species. Low salinities and high-frequency dredging confines foraminiferal proliferation. Over 40 years, changes in hydrodynamic conditions induced assemblage modifications.